Study on Mechanical Behavior of Jurassic Frozen Sandstone in Western China Based on NMR Porosity - Maoyan Ma; Yishun Huang; Guangyong Cao; Jian Lin; Shiliang Xu (Journal of Chemistry)
Study of frozen rock mechanical properties is necessary for safe application of the artificial ground freezing method in excavation of Chinese western water-rich soft rock layers. Triaxial compression tests and NMR test for samples from the western Jurassic sandstone were performed to investigate rock mechanical properties affected by low temperature and confining pressure. The results show mechanical parameters such as peak strength, cohesion, internal friction angle, residual strength, and elasticity modulus increased with the decreasing temperature under stable pressure, and the above parameters increased with the increasing confining pressure at a certain temperature. In particular, the growth rate of the rock strength would decline when the temperature was below −10°C in this study. Strength attenuation coefficients increased with the decreasing temperature, which indicated higher brittleness, whereas plastic characters got more obvious with the increasing confining pressure at a stable temperature. Furthermore, during the first two freezing stages, porosity decreased sharply with obvious increase of pore (crack) ice content, while porosity varied little at the third stage, which was the reason for the growth rate of rock strength declining with continuous low temperature from microcosmic point of view.